The Impact of Central Bank Digital Currency: How to Prevent Banking Disintermediation - Vinuela, Carlos; Sapena, Juan (Transformations In Business & Economics, 2024)
This article analyzes the effectiveness of measures to reduce the risk of bank breakdowns that have arisen with the introduction of two new types of money: the Central Bank Digital Currency (CBSV) and the CBSV-backed stable cryptocurrency. Firstly, we apply the taxonomy of money and the structure of the sectoral balance in order to compare the basic form of money in the current economies - bank deposits - with these two new types of money, which are superior to bank deposits under certain conditions. Secondly, we are dealing with the issue of the fragmentation of banks arising from digital expansion, paying particular attention to how the introduction of stable cryptocurrency supported by CBSV and CBSV can further increase this risk. Finally, we examine the effectiveness of five measures that central banks can use to reduce the risk of bank breakdowns and propose an optimal combination of these measures.